كاریگه‌رییه‌تى رۆژنامه‌گه‌رى مۆبایل"مۆجۆ" له‌سه‌ر پیشه‌ى رۆژنامه‌نووسیدا - ئه‌حمه‌د, فواد عه‌لى (Sulaimani Journal for Humanities, 2022)
Nowadays, the cellphone has become more effective device among electronic devices in the area of media. Smartphone has a special space in the world of new media, and it has become an independent media section entitled mobile press. For the easiness use of the cellphone in compare to othe media tools such as press(journal) TV, and radio it has an effective ability to prepare news reports in a way everyone or every group can exchange and transfer information in an easy way through the personal cellphone in the heart of the even especially by the journalist. At the end the researcher tries to find out how the kurdish journalist get benefit from the new technology especially in the area of directing, adapting both audio and video, as well as managing direct meeting.